Tradition and Innovation in an Ultra-Orthodox Community: The Hasidim Of Outremont - Schnoor, Randal F. (Canadian Jewish Studies / Études juives canadiennes, 2002)
Like other insular religious movements such as Hutterites andAmish, Hasidic communities are faced with the challenge ofpreserving their distinctive ideals in a technologicallyadvanced, capitalist world. Studies done in the 1960s and 1970sdocumented the success of Hasidim in safeguarding theirconvictions and creating well-functioning communities incontemporary North America. Recent evidence has demonstrated,however, that unprecedented growth rates are presenting significant challenges to Hasidim trying to sustaintheir way of life. Focusing on a case-study of the Hasidiccommunity of Outremont, a residential neighbourhood incentral Montreal, this paper outlines the social and economicchallenges facing the community and argues that, while someimportant changes have been implemented, there is a need tomodify survival strategies further in order to maintain communityviability.